Development of realistic mathematics education-based worksheets to facilitate mathematical connection abilities on pythagorean theorem material - Nadeak, Devi Irawaty; Murni, Atma; Heleni, Susda (Program Studi Pendidikan Matematika Universitas Pasir Pengaraian, 2024)
This study aimed to develop a student worksheet on the Pythagorean Theorem utilizing the Realistic Mathematics Education (RME) approach, designed to meet validity and practicality standards to enhance the mathematical connection abilities of 8th-grade students. The research adopted the 4D development model, which includes the stages of Define, Design, Develop, and Disseminate. To ensure the validity of the student worksheet, three experts conducted a comprehensive validation process. Feasibility data were collected through trials involving 8th-grade students. The validation results indicated a score of 90.77%, categorized as